Penerapan Metode RUP dalam Pengembangan Sistem Kepegawaian di Perusahaan Media Massa Palembang - Dumyati, Ahmad; Farisi, Ahmad (Universitas Multi Data Palembang, 2025)
The employee information system is a crucial element in enhancing efficiency, effectiveness, and productivity in human resource management. This study focuses on PT. Citra Bumi Sumatera, where employee data management is still conducted manually, leading to inaccuracies and delays in decision-making. The main issues include recruitment processes, work permits, leave applications, promotions, demotions, and the reward and punishment system. To address these problems, the PT. Citra Bumi Sumatera Employee System was developed as a web-based application featuring attendance tracking, document management, leave requests, and employee data management. The system was built using the Rational Unified Process (RUP) methodology, with data collected through interviews, observations, and literature studies. The study results indicate that this system improves efficiency and accuracy in the company's employee data management.